AS DIRETRIZES CURRICULARES DO MUNICÍPIO DE ANDRADINA-SP E A BASE NACIONAL COMUM CURRICULAR NA PERCEPÇÃO DOS(AS) PROFISSIONAIS DA EDUCAÇÃO INFANTIL - Eneida Aparecida Pereira Berti da Silva (2021)
The present work seeks to analyze the relationships of the National Curriculum Comum Base (BNCC) for Infant Education with the construction and implementation of the Paulista Curriculum and the Municipal Directorates of Andradina, São Paulo, their ideological, social, cultural and teacher training implications for both . Our research, from a qualitative approach (BOGDAN; BIKLEN, 2013), seeks to achieve the following objectives: a) analyze the Curricular Guidelines proposed for Infant Education, not the Municipality of Andradina and the Paulista Curriculum - Infant Education, verifying continuities and / or ruptures com to BNCC approved in 2017 and the national curricular policies developed for this educational stage in the years 1990 and 2000; b) identify and understand the perception of two infant education educators about BNCC and the proposed Curricular Guidelines for Infant Education in the Municipality of Andradina-SP developed from BNCC; c) disclose the policies of continuous training in the Municipality of Andradina / SP, for the development of the BNCC and the curriculum, analyzing the possible influences of educational policies proposed by the União. Or a theoretical reference for the analysis of the State and the curricular policy based on the texts of Antônio Gramsci (2004, 2007, 2011), Mészáros (2002), Saviani (2011) and Libâneo (2018). Or study was developed in three phases. A bibliographic phase opens or raising the scientific production on the basis of indexation (Scielo.br; Scholar Google; Bank of theses and dissections of Capes; BDTD) on the BNCC in children's education. The documentary phase was analyzed as three verses of BNCC, as Curricular Guidelines of the municipality of Andradina and the Paulista Curriculum - Infant Education. A queue in the field was carried out together with the pedagogical coordinators and the educators of the Infant Education of the municipal network of Andradina, who will carry out the investigation, from the authorization of the Secretary of Education and observed the ethical care. Therefore, it was developed to focus group technique, with the use of Google Meet, and the information collected for analysis following the guidelines of the Analysis of Context by Bardin (2016). The results show that the continuous training of the municipal network is aimed at the appropriation of BNCC, with the strong influence of Organizações Não Governamentais (NGOs) financed by private groups, including prompt materials and training of local trainers to disseminate the competences and skills of BNCC. The Municipal Directorates, as well as the Paulista Curriculum, are prepared based on the pressures of the BNCC, including the curricular organizer of these documents, following the same proposal, as well as a reference matrix and focused on competencies and skills. As Infant Educators and Pedagogical Coordinators perceive BNCC as a proposition of a common curriculum to heal educational inequalities in the country, they consider that the same “force of law” must be followed on the basis of its collection of external evaluations. It was concluded that the Municipal Curriculum Guidelines were fully aligned with the Paulista Curriculum in BNCC, or demonstrated the absence of local autonomy and rupture with the educational policies developed in the years 2000.